Building database of WEBGIS for the exchange of marine data between Vietnam and ASEAN countries - Cuong, Do Huy (Vietnam Journal of Marine Science and Technology, 2019)
The system of oceanic database management and exchange is built with the purpose of exchanging the oceanic data between Vietnam and other ASEAN countries. The system can meet the demand of sharing and exchanging oceanic data through internet connection between Vietnam and ASEAN member countries. Besides, the system of oceanic database management and exchange can meet the demands of researches, managements and share of data domestically and internationally. In this paper, we focused on the details of the system of oceanic database management and exchange, such as hardware and software, data storage, data format and data structure, data management and integration, and other issues of interface, security, standards. The WEBGIS oceanic thematic database is properly built and managed for exchanging data domestically and with other ASEAN countries.